Point contact studies of the superconducting gap of CeRu₂ - Naidyuk, Yu.G.; Moskalenko, A.V.; Yanson, I.K.; Geibel, C. (Физика низких температур, 1998)
The measured dV/dI(V) curves of point contacts between the intermetallic compound CeRu2 in the superconducting state and the normal metal Cu correspond fairly well to the Blonder-Tinkham -Klapwijk model. It is used to obtain temperature and magnetic field dependence of the superconducting gap D. The D(T) dependence corresponds well to the BCS theory with 2D(0)/kbTc*=3.1±0.1. Additionally, a region of gapless superconductivity between Tc*»4,4-5,4K and Tcbulk»6.2K is found. The gap decreases approximately linearly in a magnetic field and vanishes in a field Bc*»3.5T, which is well below the upper critical field Bc2»6T and close to the irreversibility field.